Petunidin-3-glucoside supplementation causes sex-specific effects on the lifespan and motor function in \(Drosophila melanogaster\) - Bernardo, Maria Clarissa S.; Delos Santos, Christianna Ella P.; Mabalot, Mark Edrex R.; Nas, John Sylvester B. (Academia Journal of Biology, 2024)
Petunidin-3-glucoside (P3G), an anthocyanin prevalent in vegetables, fruits, and wine, possesses noteworthy antioxidant properties attributed to its capacity to scavenge free radicals. This property has sparked interest in the potential for anthocyanins to confer benefits on longevity and age-related motor dysfunctions. In this study, the impact of petunidin-3-glucoside (P3G) on the lifespan and motor function in Drosophila melanogaster was examined, both in the presence and absence of neurotoxic substances, such as glyphosate or ethanol. Varying concentrations of P3G were incorporated into the flies' diet immediately after hatching. Subsequently, distinct sets of flies were subjected to diverse conditions, including a stress-free environment, ethanol exposure, and glyphosate exposure. The survival rate of the flies was monitored daily, and their motor function was assessed using a negative geotaxis assay on days 1, 5, 10, and 15 post-eclosion. Only male flies exhibited an extended lifespan under normal and ethanol-exposed conditions. While P3G did not induce significant alterations in overall motor function for male and female flies across various conditions, intriguing variations were observed at different time points. In female flies, low concentrations of P3G seemed to exacerbate motor function decline during mid to late adulthood, particularly in the presence of glyphosate. Conversely, middle P3G concentration improved motor function in male flies during early to mid-adulthood, a trend consistent regardless of neurotoxic exposures. Taken together, the findings underscore the potential sex-specific effects of P3G on both lifespan and motor function, with observed benefits predominantly applicable to male flies. Nonetheless, while suggestive, a more in-depth investigation is imperative to comprehensively determine whether the advantageous impact of P3G on motor function is exclusive to the early to mid-adult stage. As such, this study presents a foundation that warrants further investigation.